CoV-RBD121-NP Vaccine Candidate Protects against Symptomatic Disease following SARS-CoV-2 Challenge in K18-hACE2 Mice and Induces Protective Responses That Prevent COVID-19-Associated Immunopathology - Jennifer K. DeMarco (MDPI AG, 2021)
We developed a SARS-CoV-2 vaccine candidate (CoV-RBD121-NP) comprised of a tobacco mosaic virus-like nanoparticle conjugated to the receptor-binding domain of the spike glycoprotein of SARS-CoV-2 fused to a human IgG1 Fc domain. CoV-RBD121-NP elicits strong antibody responses in C57BL/6 mice and is stable for up to 12 months at 2–8 or 22–28 °C. Here, we showed that this vaccine induces a strong neutralizing antibody response in K18-hACE2 mice. Furthermore, we demonstrated that immunization protects mice from virus-associated mortality and symptomatic disease. Our data indicated that a sufficient pre-existing pool of neutralizing antibodies is required to restrict SARS-CoV-2 replication upon exposure and prevent induction of inflammatory mediators associated with severe disease. Finally, we identified a potential role for CXCL5 as a protective cytokine in SARS-CoV-2 infection. Our results suggested that disruption of the CXCL5 and CXCL1/2 axis may be important early components of the inflammatory dysregulation that is characteristic of severe cases of COVID-19.